Trans mRNA splicing in trypanosomes: cloning and analysis of a PRP8-homologous gene from Trypanosoma brucei provides evidence for a U5-analogous RNP. - Lücke, S (1997)
In trypanosomes all mRNAs are generated through trans mRNA splicing, requiring the functions of the small nuclear RNAs U2, U4 and U6. In the absence of conventional cis mRNA splicing, the structure and function of a U5-analogous snRNP in trypanosomes has remained an open question. In cis splicing, a U5 snRNP-specific protein component called PRP8 in yeast and p220 in man is a highly conserved, essential splicing factor involved in splice-site recognition and selection. We have cloned and sequenced a genomic region from Trypanosoma brucei, that contains a PRP8/p220-homologous gene (p277) coding for a 277 kDa protein. Using an antibody against a C-terminal region of the trypanosomal p277 protein, a small RNA of approximately 65 nucleotides could be specifically co-immunoprecipitated that appears to be identical with a U5 RNA (SLA2 RNA) recently identified by Dungan et al. (1996). Based on sedimentation, immunoprecipitation and Western blot analyses we conclude that this RNA is part of a stable ribonucleoprotein (RNP) complex and associated not only with the p277 protein, but also with the common proteins present in the other trans-spliceosomal snRNPs. Together these results demonstrate that a U5-analogous RNP exists in trypanosomes and suggest that basic functions of the U5 snRNP are conserved between cis and trans splicing.